State-owned banks in the market for corporate control. Issue 2 (3rd April 2019) - Bacchiocchi, Emanuele; Ferraris, Matteo; Florio, Massimo; Vandone, Daniela
Abstract : We study the pre-deal characteristics of state-owned banks acquiring other companies, relative to their private counterparts. We build a unique international data-set of 3682 deals in the years 2003–2013. Econometric results highlight that those state-owned banks that are acting as acquirers have an ex-ante performance similar to their private benchmarks. The results are driven by the role of development banks. This new finding points to the recent evolution of some types of contemporary state-owned financial players.